Looking at mechanobiology through an evolutionary lens. (February 2022) - Radin, Ivan; Haswell, Elizabeth S.
Abstract: Mechanical forces were arguably among the first stimuli to be perceived by cells, and they continue to shape the evolution of all organisms. Great strides have been made in recent years in the field of plant cell and molecular mechanobiology, in part owing to focused efforts on key model systems. Here, we propose to enrich such work through evolutionary mechanobiology, or 'evo-mechano', and describe three major themes that could drive research in this area. We use plastid evo-mechano as a case study, describing how plastids from different lineages perceive their mechanical environments, how their mechanical properties vary across lineages, and their distinct roles in graviperception. Finally, we argue that future research into the biomechanical properties and mechanobiological signaling mechanisms that have been elaborated by green species over the past 1.5 billion years will help us understand both the universal and the unique adaptations of plants to their physical environment.